Characteristics of the Use of Organic Mulch Sheets on Weed Growth in Caisim Mustard (Brassica juncea L.) - Theo Nicodemus Tarigan; Chaula Lutfia Saragih; Agus Susanto Ginting (Indonesian Journal of Agriculture and Environmental Analytics, 2026)
This study aims to analyze the physical characteristics of organic mulch sheets made from banana stalks, water hyacinth, and a combination of both, as well as to evaluate their effectiveness on soil microclimate, weed growth, and the yield of Chinese cabbage (caisim) in the highlands of Karo Regency. The study employed an experimental design using a non-factorial Randomized Block Design (RBD) with four treatments and three replications. The observed variables included the physical properties of the mulch, the degree of degradation, soil coverage effectiveness, weed growth, and crop yield during the study’s observation period. Data were analyzed using an F-test at the 5% significance level and the BNJ test. The results showed that the organic mulch mixture of banana stalks and water hyacinth (1:1) had the best physical characteristics, with a tensile strength of 0.9761 MPa, elongation of 1.47%, and Young’s modulus of 15.7532 MPa, as well as the lowest damage rate (45%) and the highest soil coverage effectiveness (80%). The use of organic mulch had a significant effect on suppressing weed growth compared to no mulch. The mixed mulch produced the lowest number of weeds, at 28.33 individuals, and the lowest weed weight, at 6.33 g. However, differences in mulch type did not have a significant effect on the weight of the Chinese cabbage plants. Overall, a mulch mixture of banana leaves and water hyacinth is recommended as the most effective organic mulch alternative for weed control in Chinese cabbage cultivation.